70 years after the 1948 Civil War, José Figueres in Mexico - Moreno Rodríguez, Laura Beatriz (2018)
The purpose of this work is to highlight the activities carried out by José Figueres during his exile in Mexico. Likewise, the role of the Mexican Embassy in Costa Rica during the conflict that resulted in the 1948 Civil War is shown. The thread of this work and the considerations are shown in a Colophon that invites reflection to 70 years of the Civil war as this conflict crossed national borders and was part of the Cold War.